Repurposing Lesogaberan to Promote Human Islet Cell Survival and β-Cell Replication - Jide Tian; Hoa Dang; Angela Hu; Willem Xu; Daniel L. Kaufman (Journal of Diabetes Research)
The activation of β-cell’s A- and B-type gamma-aminobutyric acid receptors (GABAA-Rs and GABAB-Rs) can promote their survival and replication, and the activation of α-cell GABAA-Rs promotes their conversion into β-cells. However, GABA and the most clinically applicable GABA-R ligands may be suboptimal for the long-term treatment of diabetes due to their pharmacological properties or potential side-effects on the central nervous system (CNS). Lesogaberan (AZD3355) is a peripherally restricted high-affinity GABAB-R-specific agonist, originally developed for the treatment of gastroesophageal reflux disease (GERD) that appears to be safe for human use. This study tested the hypothesis that lesogaberan could be repurposed to promote human islet cell survival and β-cell replication. Treatment with lesogaberan significantly enhanced replication of human islet cells in vitro, which was abrogated by a GABAB-R antagonist. Immunohistochemical analysis of human islets that were grafted into immune-deficient mice revealed that oral treatment with lesogaberan promoted human β-cell replication and islet cell survival in vivo as effectively as GABA (which activates both GABAA-Rs and GABAB-Rs), perhaps because of its more favorable pharmacokinetics. Lesogaberan may be a promising drug candidate for clinical studies of diabetes intervention and islet transplantation.